Simulation of Active Layer Dynamics, Upper Kolyma, Russia, using the Hydrograph Hydrological Model. (2nd November 2014) - Lebedeva, Liudmila; Semenova, Olga; Vinogradova, Tatyana
ABSTRACT Freeze/thaw simulations were performed for seven permafrost sites at the Kolyma Water Balance Station (KWBS), northeast Russia, using the hydrological model Hydrograph equipped with a heat transfer analytical solution that accounts for soil profile phase changes. The study sites include slopes and plateaus with thaw depths of 0.5 to 1.8 m. Landscape conditions are characterised as rocky talus, mountain tundra with dwarf tree brush, moss‐lichen cover and sparse‐growth forest or larch forest. Soil horizons are distinguished as moss‐lichen cover, peat layer, clay with a high stone content and weathered clayey shale. Schematisation of soil‐vegetation profiles and model parameters were developed for each landscape. Parameterised model output was verified using time series of observed active layer thickness for the period of 1950 to 1990. The simulated values agree well with the observed values at the study sites. The results suggest that the soil profile schematisation and model parameters, along with the proposed algorithm of heat transfer, effectively simulate active layer dynamics under various landscape conditions at the KWBS and are suitable for hydrological modelling in the permafrost zone. The modelling efforts and results are highly relevant because the natural conditions at the KWBS are representative of large areas of northeastern Russia. Copyright © 2014 John Wiley & Sons, Ltd.